Performa Produksi dan Reproduksi Ayam Sentul dengan Konsentrasi IgY Berbeda dalam Serum Darah - Ariyanti, R.; Ulupi, N.; Suryati, T.; Arifiantini, R. I. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2017)
This study was aimed to evaluate the effect of different IgY concentrations on the production performance and quality of semen sentul cocks with different total IgY in serum. This research used 20 sentul cocks with 4 month age consisted of 10 cocks with high IgY concentration and 10 cocks with low IgY concentration. Variabels observed included production performance (feed consumption, weight gain of feed conversion, final body weight, mortality) and quality semen (macroscopic and microscopic). Study was designed using completely randomized design (RAL) with 2 treatments. All treatments were repeated 10 times. The results started that IgY concentrations treatment did not affect DMA production performance and quality of semen, but signicantly affecting (p<0.05) mass movement of spermatozoa.